The Factors Affecting Filipino Grade 11–12 students’ Pronunciation - Osias Kit T. Kilag; Viquelyn A. Engbino; Cara Frances K. Abendan; Joane B. Cuizon; Dominique Q. Pahayahay (Ridwan Institute, 2023)
This study aims to examine the factors affecting students' pronunciation in English as a Second Language (ESL) among senior high school students and their English teachers. A mixed-method approach was employed, which involved a survey questionnaire and semi-structured interviews with 10 senior high school students and 10 English teachers from PAU Excellencia Global Academy Foundation, Inc. in the Philippines. The results showed that attitude, exposure, mother tongue, and instruction are factors that affect students' pronunciation in ESL. The participants agreed that attitude towards learning English greatly impacts pronunciation improvement, and that exposure to English through media and social interactions is beneficial. However, the influence of the mother tongue on pronunciation was found to be significant, particularly in the Philippines where English is taught as a second language. Furthermore, the instruction provided by teachers was found to be a crucial factor affecting students' pronunciation, with the need for teachers to utilize more effective teaching techniques and strategies. This study contributes to the literature on ESL pronunciation by examining the unique perspectives of both students and teachers in the Philippines, which can provide insights into the development of more effective ESL teaching and learning approaches. The findings can also aid in the development of curriculum design and teacher training programs to improve ESL pronunciation instruction.